Information recovery from low coverage whole-genome bisulfite sequencing - Emanuele Libertini (Nature Portfolio, 2016)
Here, Libertini and colleagues devise a computation tool that can analyze whole-genome bisulfite sequencing (WGBS) data to recover of ∼30% of the lost differential methylation position information. They use COMETgazer and COMETvintage to analyze 13 diffferent methylome data to demonstrate their performance.